Viraemic transmission of Crimean-Congo haemorrhagic fever virus to ticks. - Shepherd, A. J. (Cambridge University Press, 1991)
In order to determine the way in which vertebrates infected with Crimean-Congo haemorrhagic fever (CCHF) virus and potential ixodid tick vectors interact in nature, immature and adult ticks of several species were fed on viraemic mammals and then assayed for virus content at varying times after feeding. CCHF virus was not isolated from ticks of six species tested after feeding as adults and immature forms on sheep with viraemia of 10(2.5-3.2) LD 50/ml, nor from larval ticks fed on guinea-pigs and white-tailed rats with viraemia of 10(1.9-2.7) LD 50/ml. In contrast, virus was isolated from 10 of 152 pools of engorged adult ticks of 5 species that fed on cattle with viraemia of 10(1.5-2.7) LD 50/ml and from 3 of 137 female ticks after oviposition. Infection was transmitted to larval and nymphal Hyalomma truncatum and H. marginatum rufipes, but not to Rhipicephalus evertsi evertsi, from a scrub hare with viraemia of 10(4.2) LD 50/ml but only nymphal H. truncatum and H. m. rufipes became infected from scrub hares with viraemia of 10(2.6-2.7) LD 50/ml. Infection was transmitted trans-stadially in H. m. rufipes and H. truncatum infected as nymphae, and adult H. m. rufipes transmitted infection to a sheep. No evidence of transovarial transmission was found in larval progeny of ticks exposed to CCHF virus as adults on sheep and cattle or as immatures on scrub hares.